Challenge at the Edge: Long-Term Sea Level Rise vs. Short-Term Extreme Events - Gary B. Griggs (Journal of Marine Science and Engineering, 2025)
California and most other coastlines around the nation and the world are being impacted by both long-term sea-level rise (SLR) and short-term extreme events. Global sea level over the last 10 years of satellite altimetry has averaged approximately 4.1 mm/yr. (~16 in./100 yrs.), although this rate is accelerating at about 1.2 mm/yr. per decade. Projections of future sea levels have now been developed by many different agencies, organizations, and committees, and cluster around 12 inches by 2050. Over the near term, however, until mid-century, and likely beyond, it will be the short-term extreme events such as hurricanes along the U.S. Atlantic and Gulf coasts, and the coincidence of very large waves and high astronomic tides along the U.S. Pacific coasts that will pose the major threat to both public infrastructure and private development.